Role of Hydrogen Peroxide (H2O2) Enhanced Anaerobic Co-digestion of Petrochemical Wastewater on Cycle Time Minimization During Biomethanation - Siddique, Md. Nurul Islam; Mimi Sakinah, A. M.; Zularisam, A. W. (Academic Journals, 2013)
The latent of per-oxidation pretreatment to petrochemical waste water (PWW) prior to anaerobic co-digestion process was explored in continuous stirred tank reactor (CSTR) continually with dairy cattle and beef cattle manure. Oxidation by hydrogen peroxide (OHP), elevated biodegradability index (BOD/COD) up to 35%. While CSTR operated with non-OHP PWW, system was found to be failed at organic loading of 6.5 to 12.99 kg COD/m3/day due to vigorous volatile fatty acid accumulation. Inversely, the OHP PWW rendered sustainable superior TCOD removal at 6.03 to 11.7 kg COD/m3/day organic loading with durable process stability at co-digestion period. As methane production is considered to be inhibited due to volatile fatty acid (VFA) accumulation leading to instability of reactor operation during anaerobic digestion, the co-digestion of OHP pretreated PWW resulted in exaggerated methane yield, followed by 98 ± 0.5%, 95 ± 0.05% and 79 ± 0.06% COD reduction at 9, 6 and 4 days HRT. The concrete data revealed that prolonged HRT and abridged cycle time (CT) caused CSTR aggrandized TCOD removal efficiency and methane yield.